EFISIENSI PRODUKSI DAN PENDAPATAN USAHATANI TEMBAKAU DI KABUPATEN LAMPUNG TIMUR - Estariza, Erzia; Prasmatiwi, Fembriarti Erry; Santoso, Hurip (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This study aims to analyze the production’s efficiency of tobacco in East Lampung Regency, determine the factors that influence the technical efficiency of tobacco farm in East Lampung Regency, and determine the amount of tobacco farming income in East Lampung Regency. The research was conducted in proposive selected two districts, namely Batanghari Nuban and Purbolinggo of East Lampung Regency. The samples were drawn from the population by simple random design, resulted a total sample of 60 tobacco’s farmers. The analyses used in this research were descriptive qualitative and quantitative analysis. The first purpose was answered by using frontier production function, the second by multiple linear regression analysis and the third by employing income analysis. The results showed that tobacco farming in East Lampung Regency was not technically efficient, technical efficiency of farming in East Lampung Regency was 73,85%. The factors that influence significantly in technical efficiency of tobacco farm in East Lampung Regency was farming experience, formal education, counseling frequency and spacing of tobacco. Tobacco farming in East Lampung Regency was profitable because it had a value of R/C=1.85 and income Rp20,934,062.12 per hectar. Keywords: efficiency, frontier, income, tobacco farming